The Externalities of Inequality: Fear of Crime and Preferences for Redistribution in Western Europe. Issue 2 (21st August 2015) - Rueda, David; Stegmueller, Daniel
Abstract : Why is the difference in redistribution preferences between the rich and the poor high in some countries and low in others? In this article, we argue that it has a lot to do with the rich and very little to do with the poor. We contend that while there is a general relative income effect on redistribution preferences, the preferences of the rich are highly dependent on the macrolevel of inequality. The reason for this effect is not related to immediate tax and transfer considerations but to a negative externality of inequality: crime. We will show that the rich in more unequal regions in Western Europe are more supportive of redistribution than the rich in more equal regions because of their concern with crime. In making these distinctions between the poor and the rich, the arguments in this article challenge some influential approaches to the politics of inequality.